Seasonal occurrence and offshore accumulation of phycotoxins in a subtropical semi-enclosed bay: Insights from a year-round survey in Qinzhou Bay, South China Sea - Hui-Xia Geng; Zhuo-Ru Lin; Wen-Jiao Tang; Sara A. Cunha; Zhen-Jun Kang; Xiao-Tian Han; Jin-Xiu Wang; Ren-Cheng Yu (Marine Pollution Bulletin, 2026)

SMART-guided discovery of anti-adipogenic guaiane sesquiterpenoids from the roots of Edgeworthia gardneri - Ming-Cui Yang; Lin-Lin Tian; Xiu-Qing Song; Yao-Yue Fan (Phytochemistry, 2026)

From astrocyte cholesterol synthesis to synaptic dysfunction: mechanisms of neuron-glia lipid coupling - Muhammad Mateen Tahir; Xiu Liu; Lin-Sheng Yi; Xiao-Qing Hou; Qin Liao; Hua-Li Yu (Molecular Biology Reports, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

From black box to transparency: Explainable artificial intelligence driven origin identification of Xinjiang Nilka black bee honey - Xiao-Hui Sun; Lin-Hua Shi; Xiang-Shuai Li; Xiu-Ying Tang; Hong-Song Ren; Sheng-Hong Liu (Food Chemistry, 2026)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

Acid leaching-enhanced iron and nitrogen co-doped carbocatalysts for peroxydisulfate activation: Promoting phenol removal via polymerization - Luo Wang; Jiayi Xu; Wei Zhang; Xiaochong Wang; Wenli Shao; Mingyue Lin; Toru Murayama; Guangli Xiu (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

ANN-assisted interfacial engineering of MOFs heterostructures for synergistic CO2 photoreduction and antibiotic elimination - Fan Ye; Zhe Lin; Xu-Chao Xia; Ting Zou; Jin-Yu Dai; Lin Zhang; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2026)

Physical morphology of conductive carriers shapes anaerobic biofilm development and methanogenesis - Lu Zhang; Wen He; Zu-xiang Yan; Tong-yi Yang; Lin-zhi Zhai; Xiu-jie Wang; Qian-qian Jia; Ze-chong Guo (Bioresource Technology, 2026)

Two new chroman derivatives from the desert plant endophytic fungus Lasiodiplodia sp - Wen-Xiang Tao; Jin Ye; Lin-Ping Zhang; Le Zhang; Dong-Yang Liu; Xiu-Feng Yang; Tian-Cheng Ma; Yi Sun; Chang Zhang; Fan-Wei Liu; Ying Chen; Bo Song (Natural Product Research, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Two new monoterpene glycosides from the endophytic fungus Diaporthe nobilis and their cytotoxic effects - Ying Chen; Jian Wang; Cai-Lin Zhao; Xiu-Feng Yang; Jin Ye; Lin-Ping Zhang; Yun-Xiao Li; Fan-Wei Liu; Le Zhang; Bo Song (Natural Product Research, 2026)

Effect of subsurface barrier on hydrological and stratigraphic alterations during engineering groundwater control - Xiu-Li Xue; Hao-Ying Lin; Chao-Feng Zeng; Gang Zheng; Zu-Hao Zhang; Lei Han; You-Wu Zhao (Journal of Hydrology, 2026)

Deciphering peroxydisulfate vs. peroxymonosulfate activation by biochar catalysts via explainable machine learning - Xiaochong Wang; Wei Zhang; Ruobing Cheng; Pengyuan Ma; Junhui Su; Mingyue Lin; Toru Murayama; Guangli Xiu (Journal of Hazardous Materials, 2026)

Cretaceous sediment provenance, dispersal systems, and tectono-paleogeography of the western Tarim Basin, Northwest China: Far-field effects of Neo-Tethyan flat subduction - Hong-Xiang Wu; Feng-Qi Zhang; Cai-Yun Wang; Xiao-Gan Cheng; Kai-Xuan An; Yildirim Dilek; Cai Chen; Yu-Qing Zhang; Xiu-Bin Lin; Shuan-Hong Zhang; Han-Lin Chen (Global and Planetary Change, 2026)

Breaking the sensitivity barrier in ELISA: A molecularly engineered peptide nanointerface achieves ultrasensitive detection of zearalenone - Zijun Yang; Zhiwei Liu; Zhongqi Lin; Wenjuan Xu; Xiu'an Duan; Zhenlin Xu; Xiangmei Li (Analytica Chimica Acta, 2026)

Static magnetic field-assisted fermentation of corn dietary fiber by Hericium erinaceus: Insight into fermentation mechanisms and related characteristics - He Ban; Jingwei Wang; Ding Xu; Xiangmeng Yin; Wei Li; Lin Xiu; Dan Cai; Jingsheng Liu (Food Chemistry, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Exploring gut microbiota responses to low-dose thallium exposure via food chain transfer: insights from soil–plant–human systems - Lu-Xiu Lin; Wei-Jun Chen; Shun-Xing Li; Feng-Ying Zheng; Xu-Guang Huang; Feng-Jiao Liu; Jia-Yi Luo; Zhao-Jing Huang; Wen-Jie Zhang; You-Bin Zhuo; Xin Long (Environmental Geochemistry and Health, 2026)

Nano zero-valent iron-modified biochar regulates soil carbon mineralization and stability across aggregates in alpine degraded grassland - Yao Li; Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Feida Sun; Jinchao Gong; Shijie Zhou; Zhouwen Ma; Chengjing Wu; Lin Liu; Ran Xue; Yue Xiu; et al. (Soil Ecology Letters, 2026)

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Static magnetic field assists corn germination: Changes in nutritional composition and improvement of functional properties - Xin Jiang; Yelinxin Chen; Xiaoxi Yu; Jingwei Wang; Ding Xu; Huimin Liu; Dan Cai; Lin Xiu; Jingsheng Liu (Food Chemistry, 2026)

Quality formation in corn kernels during postharvest ripening: the influence of storage conditions on phenolic components and antioxidant activity - Fuyin Zhao; Haohai Li; Rixin Zang; Jiahui Pan; Jinying Zhu; Lin Xiu; Huimin Liu; Mingzhu Zheng; Meihong Liu; Jingsheng Liu (Food Chemistry, 2026)

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

PLGA nanoparticles encapsulating fibroblast growth factor 21 alleviate acetaminophen-induced acute liver injury - Jie Lin; Guoxin Jin; Ling Zhang; Xiu Weng; Kecheng Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Development of Two Multienzyme Isothermal Rapid Amplification Techniques for the Rapid Visual Detection of Micropterus salmoides rhabdovirus - Qingyue Xu; Yiping Lin; Yixia Ma; Zhantian Liao; Tao Li; Shuai Wang; Chunguo Liu; Zhan Luo; Qingqing Song; Shun Zhou; Yunji Xiu (Journal of Fish Diseases, 2026)
Largemouth bass ( Micropterus salmoides ) is an important freshwater‐cultured species in China. M. salmoides rhabdovirus (MSRV) is a devastating pathogen that causes high mortality (exceeding 90% in acute outbreaks) in largemouth bass fry, posing a severe threat to the global largemouth bass aquaculture industry. To address the urgent demand for rapid, on‐site MSRV detection, two multienzyme isothermal rapid amplification (MIRA)‐derived methods—multienzyme isothermal rapid amplification with fluorescence detection (MIRA‐FLU) and multienzyme isothermal rapid amplification with lateral flow dipstick (MIRA‐LFD)—were established and optimized targeting the conserved nucleoprotein (N) gene of MSRV. The performance of both methods was systematically evaluated, and their practical applicability was verified using clinical samples collected from diseased fish farms. The results demonstrated that both methods exhibited high sensitivity, with a detection limit of 9 copies/μL for the standard plasmid. Both detection methods demonstrated high specificity and showed no cross‐reactivity with other common aquatic viruses, indicating their high specificity for MSRV detection. MIRA‐FLU completed amplification within 25 min at 42°C, while MIRA‐LFD achieved amplification within 12 min at 37°C. MIRA‐FLU is used for real‐time fluorescent quantitative detection, whereas MIRA‐LFD enables visual, instrument‐free reading via lateral flow test strips. In comparative analyses of clinical samples, the diagnostic results of MIRA‐FLU and MIRA‐LFD were compared with those of the standard conventional PCR test and showed nearly 100% consistency. Therefore, our MIRA‐FLU and MIRA‐LFD detection methods demonstrate excellent specificity and sensitivity, providing two simple, rapid and reliable approaches for large‐scale field surveys of MSRV in resource‐limited settings.

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

MoB2 nanozyme-decorated borate hydrogels with ROS-scavenging and antibacterial abilities for infected diabetic wound healing - Yueguang Fang; Chenxi Li; Ruifang He; Lanling Xiu; Dingwen Xiao; Miao Wang; Yuesheng Dong; Lin Sun; Junwei Ye (Chemical Engineering Journal, 2026)

Preparation and Characterization of Lightweight Ceramsite from Construction Waste and Coal Fly Ash - Xue Song; Weishuang Lou; Zhengqiu Li; Bopeng Zhao; Lin Wang; Xiu Li; Yuejiao Zhang; Wenjing Sun; Yingming Zhang; Yongde Liu; Hongyun Yang (Water, Air, & Soil Pollution, 2026)

Skin Ulceration in Farmed Leopard Coral Grouper (Plectropomus leopardus) Was Associated with Vibrio spp. and Photobacterium damselae in China - Yunji Xiu; Xiaowan Lin; Lirong Jiang; Zemin Bai; Jinlong Dong; Jinjing Cao; Xiuxiu Tian; Yu Zhang; Wei Wang; Ying Huang; Bo Zhou; Lei Wang; et al. (Fishes, 2026)
The leopard coral grouper (Plectropomus leopardus), an economically important marine fish, is widely farmed in Hainan Province, China. However, intensive farming has led to frequent disease outbreaks, including viral nervous necrosis, vibriosis, and enteritis, with skin ulceration a widespread and significant concern. To identify the pathogen causing skin ulceration, we collected diseased fish from Hainan and conducted histopathological and ultrastructural analyses, parasite examination, viral metagenomic sequencing, and bacterial isolation and identification. The histopathological analysis and ultrastructural observation showed that the diseased P. leopardus displayed marked pathological alterations, with significant hepatic degeneration and necrosis and splenic structural disorganization. Parasites and viruses were both excluded from being the primary pathogen. A total of 79 bacterial strains were isolated from diseased P. leopardus liver tissue, including Vibrio harveyi (38 strains, 48.1%), Vibrio owensii (17 strains, 21.5%), Vibrio rotiferianus (16 strains, 20.3%), and Photobacterium damselae subsp. damselae (8 strains, 10.1%). Infection experiments suggested that all four bacterial species could induce skin ulceration. This study demonstrates that skin ulceration in P. leopardus is associated with multiple bacterial pathogens, refining the previous view that attributed the disease solely to V. harveyi. These findings provide a foundation for developing vaccines and disease-resistant breeding strategies.

Nonlinear dynamics of interactions within the soil nematode food web across a saline-alkaline gradient - Bo-Tao Liu; Jing-Nan Zhang; Lin Chen; Neil B. McLaughlin; Yang-feng Hu; Shi-Xiu Zhang; Lu-Jun Li (CATENA, 2026)

Bioactive sesquiterpene lactones with cytotoxic activity from Youngia japonica - Hao Gong; Kuan Lin; Lei Zhang; Yi Huang; Li-Juan Hu; Xiao-Ya Liu; Hao Ming; Si-Qi Wang; Qing-Qin He; Xian-Sheng Ye; Shu-Xiu Zhu (Phytochemistry Letters, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

Zein/ferulic acid/sodium alginate ternary nanoparticles: characterization and application in stable Pickering emulsions - Xu Zhang; Fangzhu Zheng; Xianglong Dai; Jingsheng Liu; Lin Xiu; Huimin Liu; Dan Cai (Food Chemistry, 2025)

Three tetraspanins, Tspan1, Tspan2A and Tspan3 from Litopenaeus vannamei involved into Vibrio parahaemolyticus infection - Yi-Qian Zhang; Shuang-Shuang Luo; Xiu-Li Chen; Ai-Jin Wang; Chao-Jie Hou; Qing-Yun Liu; Min Peng; Chun-Ling Yang; Yan Lei; Wei-Lin Zhu; Hong Liu; Yong-Zhen Zhao; et al. (Fish & Shellfish Immunology, 2025)

Synergistic effects and mechanism of recombinant viral vector-mediated STAT1 overexpression and STAT3 silencing on glioma U251 apoptosis - Xin-Long Hu; Hong Li; Guo-Dong Zhang; Chao Lin; Ping Huang; Xiu-Feng Chen; Fang Wan; Chang-Wu Dou; Hai-Tao Ju (Molecular Biology Reports, 2025)

Overlooked risks of non-oxidizing antimicrobials (NOAMs) in water environments - Nan Huang; De-Xiu Wu; Ye Du; Yan-Lin Chen; Qian-Yuan Wu; Hong-Ying Hu (Critical Reviews in Environmental Science and Technology, 2025)

Stereoelectroencephalography in temporal lobe epilepsy: clinical characteristics, influential factors, and surgical outcomes - Jiajie Mo; Xiu Wang; Xuemin Zhao; Baotian Zhao; Chao Zhang; Lin Sang; Wenhan Hu; Jianguo Zhang; Gerold Baier; Xiaoqiu Shao; Kai Zhang (Science Bulletin, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Magnesium-enriched biochar as a multifunctional carrier: unlocking productivity and stability in the algal-bacterial symbiosis system - Xiu Zhang; Xiang Cai; Xin Hu; Chenlu Zong; Hongjun Lin; Liguo Shen; Jiaheng Teng; Bisheng Li; Leihong Zhao; Meijia Zhang (Chemical Engineering Journal, 2025)

Positive effects of gamma aminobutyric acid on growth and lipopolysaccharide-induced intestinal mucosal barrier damage in snakehead (Channa argus) - Xue-qin Wu; Xu-nan Li; Feng-kun Cai; Yun-jie Lin; Xiao-tian Niu; Xiu-mei Chen; Yan-nan Tong; Gui-qin Wang (Aquaculture International, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

Novel L-type chiral metal(II) complexes inhibit breast cancer growth through synergistic effects of anti-angiogenesis, anti-inflammatory, apoptosis induction and cuproptosis - Nan Jin; Bing-Bing Xu; Hong-Yu Lin; Bing-Li Jiang; Qiao-Ying Yang; Xiu-Ying Qin (Apoptosis, 2025)

Augmented phototransformation of brominated disinfection by-products via surface water introduction during sunlit reclaimed water storage - De-Xiu Wu; Yuan-Chu Qin; Wen-Long Wang; Yan-Lin Chen; Qian-Yuan Wu (Journal of Hazardous Materials, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Screening of Antibiotic-Sensitive Lactic Acid Bacteria (LAB) Associated with the Gut of Penaeus Vannamei and its Application in Shrimp Farming - Yiwen Gu; Xiu Lin; Yanxu Lu; Shuguang Fang; Kun Hu; Xin Ju; Liangzhi Li; Zhi Chen (Current Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Detection of toluene at ppb levels using Au catalyst supported on Al-doped ZnO - Jiali Hong; Keyu Chen; Kaiping Yuan; Mingyue Lin; Qi Cao; Jialong Lin; XinLin Wang; Xiaoqian Bai; Tamao Ishida; Toru Murayama; Guangli Xiu (Journal of Environmental Chemical Engineering, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Regulation of electrode surface microenvironment by porous ion transport layer for High-Efficiency CO2 electrochemical reduction to ethylene - Hao-Yan Shi; Yan-Xin Chen; Yi-Hu Pu; Hai-Long Wang; Yi-Zhan Xie; Xin-Zhi Tian; Yang Yang; Ao-Sheng She; Wen Chen; Wei-Hua Yang; Xiu-Mei Lin; Can-Zhong Lu (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Early miocene adakitic porphyries in the Chagai arc, Pakistan: Petrogenesis, tectonic setting and implications for porphyry Cu-Au mineralization - Xiu-Quan Miao; Chuan-Dong Xue; Xue-Ping Yang; Yun-Ying Zhang; Jian-Lin Chen (Lithos, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Development and Evaluation of a Rapid Visualisation Detection Method for Ameson portunus Based on RPA ‐ LFD - Yunfei Pang; Jiaxue Song; Lirong Jiang; Yiping Lin; Yunji Xiu (Journal of Fish Diseases, 2025)
The Ameson portunus is a prevalent pathogen affecting Portunus trituberculatus , which can infect P. trituberculatus and cause albinism, seriously damaging its economic value. Therefore, there is a pressing need for an efficient detection platform to rapidly and sensitively identify A. portunus . In this study, we have developed a method known as recombinase polymerase amplification combined with lateral flow dipstick (RPA‐LFD) for the swift detection of A. portunus . Three sets of specific primer pairs and a probe were designed according to the spore wall protein (SWP) sequence of A. portunus , in which one of the primer pair (ApSWP‐F1/R1) showed the best amplification effects. The optimal reaction temperature was ultimately determined to be 39°C and the optimal reaction time was set at 10 min after careful optimisation of both variables. The sensitivity of the RPA‐LFD method was better than that of polymerase chain reaction (PCR), with a limit of 1.71 × 10 −4 ng/μL. This RPA‐LFD detection method has good specificity for the detection of A. portunus , and tests for other parasites such as Zschokkella ophiocephali , Myxobolus drjagini , Myxidium lieberkuhni and Pelteobagrus fulvidraeo are negative. The above results show that the RPA‐LFD detection method of A. portunus established in this study has strong specificity, high sensitivity, simple operation and visual results, which can be widely used for rapid detection on site.

Far-Infrared Radiation Ameliorates the Cognitive Dysfunction in an Alzheimer’s Disease Transgenic Mouse via Modulating Jak-2/Stat3 and Nrf-2/HO-1 Pathways - Wen Yang; Qiuxia Yu; Nick Wang; Koon Kit Lam; Zhi-Xiu Lin; Yan-Fang Xian (NeuroMolecular Medicine, 2025)
Alzheimer’s disease (AD) is the primary cause of dementia in the elderly. However, effective therapies that modify the disease process in AD remain elusive. Far-infrared radiation (FIR) is commonly utilized as a complementary treatment a range of disease, for example insomnia and rheumatoid arthritis. In this research, we explored how FIR light impacts the cognitive functions of TgCRND8 AD mice and elucidated its underlying molecular mechanism. The cognitive capabilities of TgCRND8 mice assessed by employing the Morris water maze. The concentrations of IL-1β, TNF-α, IL-4, Aβ40, and Aβ42 protein were assessed by enzyme-linked immunosorbent assay. Immunostaining was conducted to assess the Aβ deposits and microglial presence in the brains of TgCRND8 mice. Western blot was applied to detect the protein expressions of tau phosphorylation, amyloid-β (Aβ) production, Jak-2/Stat3, and Nrf-2/HO-1 pathways. The results indicated that FIR light notably ameliorated the cognitive impairments of the AD mice, reduced both Aβ deposition and tau protein hyperphosphorylation at sites of Thr205, Ser369, Ser404, and Thr181, suppressed the release of TNF-α and IL-1β, attenuated the ratios of p-Jak-2/Jak-2 and p-Stat3/Stat3, while increased the protein levels of IL-4, Nrf-2, and HO-1 in the brains of TgCRND8 mice. These findings amply demonstrated that FIR light ameliorated cognitive deficits of TgCRND8 mice via reducing both Aβ burden and tau protein hyperphosphorylation, suppressing the neuroinflammation, and restoring the levels of the oxidative-related proteins through modulating Jak-2/Stat3 and Nrf-2/HO-1 pathways. These experimental findings indicate that FIR light treatment is a promising treatment approach for AD.

Regulation strategies of microplastics with different particle sizes on cadmium migration processes and toxicity in soil-pakchoi system - Qirui An; Na Zheng; Changcheng Chen; Xiaoqian Li; Yining Ji; Liyuan Peng; Zhifei Xiu; Qiuyan Lin (Journal of Hazardous Materials, 2025)

Genome-wide identification and functional characterization of the Shaker potassium channel family in centipedegrass suggest their distinct roles in potassium uptake and salt tolerance - Dong-Li Hao; Jin-Yan Zhou; Jia Qu; Jun-Yi Zhai; Ying Zhao; Jian-Xiu Liu; Hai-Lin Guo; Jun-Qin Zong (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Extracting vectorized agricultural parcels from high-resolution satellite images using a Point-Line-Region interactive multitask model - Mengmeng Li; Chengwen Lu; Mengjing Lin; Xiaolong Xiu; Jiang Long; Xiaoqin Wang (Computers and Electronics in Agriculture, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Effects of static magnetic field treatment on the digestive, structural and physicochemical characteristics of germinated corn starch - Xin Jiang; Fangzhu Zheng; Jiankun Yu; Pengwen Lv; He Ban; Huimin Liu; Dan Cai; Lin Xiu; Jingsheng Liu (Food Chemistry, 2025)

Synthesis of phosphorylated covalent organic frameworks with different linkages–Critical factors controlling the extraction of uranium from highly acidic media - Xiao-Yi Tang; Hui-Di Zhang; Zi-Jie Li; Shuai Wang; Si-Yan Liu; Tao-Yuan Xiu; Ji-Pan Yu; Lin Wang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2025)

Microplastics-exposure experience aggravates the accumulation of diarrhetic shellfish toxins (DSTs) in thick-shell mussel Mytilus coruscus through impairing detoxification processes - Kuan-Kuan Yuan; Ying-Ying Yu; Yu-Jie Liu; Xiu-Lin Yang; Yan-Hang Mo; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Journal of Hazardous Materials, 2025)

Development of Three Recombinase Polymerase Amplification Assays for the Rapid Visual Detection of Spiroplasma eriocheiris - Yunji Xiu; Ruixin Feng; Zongrui Yang; Lirong Jiang; Yiping Lin; Qingyue Xu; Dong Zheng; Shun Zhou (Journal of Fish Diseases, 2025)
Spiroplasma eriocheiris is a pathogen in the Chinese mitten crab Eriocheir sinensis and is associated with tremor disease. S. eriocheiris infects virtually all artificially bred crustaceans, resulting in significant economic losses to the aquaculture industry in China. Recombinase polymerase amplification (RPA) is considered a promising technology for the rapid and sensitive detection of disease. For the rapid detection of S. eriocheiris , this study established basic RPA, RPA‐EXO and RPA‐LFD, which were visualised via agarose gel electrophoresis, SYBR Green I, fluorescence signals and test lines on lateral flow dipsticks. Specific primers and probes were designed based on the 16S ribosomal RNA sequence of S. eriocheiris . The optimal primer pairs for the basic RPA, RPA‐EXO and RPA‐LFD were RPA‐F3/R3, RPA‐F3/R3 and RPA‐LFD‐F3/R3, respectively. The optimal temperatures and times of basic RPA, RPA‐EXO and RPA‐LFD were 37°C for 25 min, 39°C for 30 min and 39°C for 10 min, respectively. The specificity test indicated that in addition to the positive test results for S. eriocheiris , the other five DNA templates tested negative, demonstrating strong specificity. The results of the sensitivity test revealed that the detection limits of RPA, RPA‐EXO and RPA‐LFD were 5.77 × 10 −2 , 5.77 × 10 −4 and 1.52 × 10 −6 ng/μL, respectively, indicating high sensitivity. This study established three methods for the detection of S. eriocheiris that are characterised by a constant temperature, rapid response, high sensitivity and strong specificity.

The role of bile acid in regulating head-kidney, spleen and skin immune function of on-growing grass carp (Ctenopharyngodon idella) - Fei Zhao; Xiu-Rong Peng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

Acidobacteria as the dominant microorganism on the nitrogen-removal wastewater treatment with a low chemical oxygen demand/ammonium nitrogen ratio in biological contact oxidation reactor - Xiu Yue; Junjie Liang; Yuting Lin; Xiaotong Xiao; Lijun Chen; Kangyuan Che; Kaixuan Xiao (Journal of Environmental Management, 2025)

Research progress of electrospinning in food field: A review - Fa-Lin Sun; Ming-Yue Zhao; Yue Li; Zhi-Ying Li; Xiu-Jun Li; Nuo Wang; Bo-Wen Hu; Hao-Yu Xue; Min Zhao; Jin-Long Tian (Food Hydrocolloids, 2025)

Retraction Note: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Microbial rrn copy number is associated with soil C: N ratio and pH under long-term fertilization - Xiu Wang; Jiahui Lin; Xinyi Peng; Yifan Zhao; Haodan Yu; Kankan Zhao; Albert Barberán; Yakov Kuzyakov; Zhongmin Dai (Science of The Total Environment, 2024)

Tissue-specific distribution and fatty acid content of PFAS in the northern Bohai Sea fish: Risk-benefit assessment of legacy PFAS and emerging alternatives - Zhifei Xiu; Na Zheng; Qirui An; Changcheng Chen; Qiuyan Lin; Xiaoqian Li; Sujing Wang; Liyuan Peng; Yunyang Li; Huicheng Zhu; Siyu Sun; Shuai Wang (Journal of Hazardous Materials, 2024)

Experimental evaluation of bonded/unbonded prestressed precast concrete joints under repetitive loading scenarios: Seismic performance and retrofit intervention - Hao Fang; Hai-Rong Shi; Xiu-Hang Li; Chun-Lin Wang; Bin Zeng (Engineering Structures, 2024)

Assessment of multidimensional diversity and conservation of threatened timber trees in China under climate change - Jian-Lin Hu; Xiu-Qin Ci; Xiao-Yan Zhang; Run Zhou; Jian-Hua Xiao; Zhi-Fang Liu; Can-Yu Zhang; Xuan Jin; Jie Li (Biological Conservation, 2024)

Comparative Analysis of Seven Endogenous Hormones in a Novel Dual-axillary Bud Mutant Genotype of Sugarcane - Kamal Priyananda Wickramasinghe; Jun Mao; Chao-hua Xu; Xiu-qin Lin; Xu-juan Li; Wei Qin; Hong-bo Liu; Xin-long Liu; Faisal Mehdi; Pei-fang Zhao; Xin Lu (Sugar Tech, 2024)
The sugarcane genotype YZ 07-86 is a distinct natural mutant with dual-axillary buds. Exploitation of this valuable trait in sugarcane breeding requires an understanding of the physiological mechanism of dual-axillary bud formation. This experiment determined the contents of indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins (GA 3 and GA 4 ), and three cytokinins (CKs), namely isopentenyl adenosine (iPA), zeatin riboside (ZR), and dihydrozeatin riboside (DHZR), in the shoot apical meristem tissues of YZ 07-86 and its sister line YZ 07-87, which served as the control genotype. The field experiment followed a completely randomized design with three replications for each genotype. Sampling was done at 5-day intervals, starting 106 days after planting. The ELISA technique was used to measure the contents of endogenous hormones. The study revealed that the mean contents of IAA, GA 3 , GA 4 , DHZR, and iPA were not significantly different ( P > 0.05) among the genotypes. Conversely, in YZ 07-86, the mean ZR content was significantly higher ( P < 0.05), and the mean ABA content was significantly lower than in the control genotype. Moreover, the mean content ratios of ZR/IAA, ZR/ABA, ZR/GA 3 , and ZR/GA 4 were also significantly higher in YZ 07-86. The study concludes that elevated ZR content and an increased ZR/ABA ratio directly contributes to dual-axillary bud formation in YZ 07-86, offering valuable insights for the advancement of sugarcane genotypes.

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Unraveling the tectonic and climatic influences on River Erosion: A late Quaternary case from the Dongda River, northeast tibet - Xiu Hu; Jinghao Lei; Weitao Wang; Yiran Wang; Youli Li; Peizhen Zhang; Kairong Lin; Wenjun Zheng; Qingri Liu; Fei Liu; Hao Liang; Yang Wang; et al. (Journal of Asian Earth Sciences, 2024)

Optimization of microalgal-bacterial consortium flocculation through chitosan-diatomite composite materials: A sustainable approach to biomass harvesting - Yu Zhao; Qian Lei; Jiaheng Teng; Xiu Zhang; Hongjun Lin; Meijia Zhang (Chemical Engineering Journal, 2024)

Phthalate monoesters accumulation in residential indoor dust and influence factors - Qiuyan Lin; Na Zheng; Qirui An; Zhifei Xiu; Xiaoqian Li; Huicheng Zhu; Changcheng Chen; Yunyang Li; Sujing Wang (Science of The Total Environment, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Impact of nickel and alkaline earth metals interaction on sustainable carbon nanotubes generation from plastic face masks via catalytic pyrolysis - Xiu-Xian Lim; Siew-Chun Low; Kai Qi Tan; Kun-Yi Andrew Lin; Chao He; Tao Zhou; Wen-Da Oh (Chemical Engineering Journal, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

MCT1-mediated transport of valeric acid promotes porcine preimplantation embryo development by improving mitochondrial function and inhibiting the autophagic AMPK-ULK1 pathway - Xiu-Li Zhang; Zhi-Yong An; Gao-Jie Lu; Tuo Zhang; Cheng-Wei Liu; Meng-Qi Liu; Qing-Xin Wei; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

First identification of Carboniferous mafic dikes during a period of arc magmatic quiescence in the Northern Qiangtang terrane, central Tibet: Back-arc extension and implications for opening of the Xijir Ulan Ocean - Zhi-Wei Yu; Wei Dan; Qiang Wang; Xiu-Zheng Zhang; Jun Wang; Bing Chen; Lin Gong (Lithos, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

Firmicutes and Bacteroidetes as the dominant microorganisms for ammonium nitrogen wastewater treatment with a low C/N ratio in BCOR - Xiu Yue; Xiaotong Xiao; Junjie Liang; Yuting Lin; Kaixuan Xiao; Kangyuan Che (Journal of Water Process Engineering, 2024)

Polystyrene nanoplastics induce cardiotoxicity by upregulating HIPK2 and activating the P53 and TGF-β1/Smad3 pathways - Jian-Zheng Yang; Kai-Kai Zhang; Clare Hsu; Lin Miao; Li-Jian Chen; Jia-Li Liu; Jia-Hao Li; Xiu-Wen Li; Jia-Hao Zeng; Long Chen; Ji-Hui Li; Xiao-Li Xie; et al. (Journal of Hazardous Materials, 2024)

Converting kitchen waste into value-added fertilizer using thermophilic semi-continuous composting-biofiltration two-stage process with minimized NH3 emission - Xiu-Lin Chu; Xiang-Yu Peng; Zhao-Yong Sun; Cai-Yun Xie; Yue-Qin Tang (Bioresource Technology, 2024)

High dimensional proteomic mapping of bone marrow immune characteristics in immune thrombocytopenia - Feng-Qi Liu; Qing-Yuan Qu; Ying Lei; Qi Chen; Yu-Xiu Chen; Meng-Lin Li; Xue-Yan Sun; Ye-Jun Wu; Qiu-Sha Huang; Hai-Xia Fu; Yuan Kong; Yue-Ying Li; et al. (Science China Life Sciences, 2024)

Caspase-12 is Expressed in Purkinje Neurons and Prevents Psychiatric-Like Behavior in Mice - Lin-Yan Huang; Yi-Ning Liu; Jie Chen; Hai-Xue Zhu; Li-Li Li; Zhi-Yan Liang; Jin-Xiu Song; Yu-Jie Li; Zhao-Li Hu; Dieter Demon; Andy Wullaert; Wan Wang; et al. (Molecular Neurobiology, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Tuning multiple enzyme-like activities by metal doping for identification and quantitation of antioxidants in cosmetics - Sheng-Tao Wu; Hui-Qi Su; Kai-Lin Shen; Ying Li; Yi Ge; Xiu-Fang Cheng; Chang-Ming Nie; Cong-Hui Wang; Ying-Wu Lin (Chemical Engineering Journal, 2024)

Constructing hydroxyoxime-functionalized ionic liquid [BHIB][NTf2] for the separation of Mo(VI) from U(VI) - Feng Liu; Tao-Yuan Xiu; Wei Jin; Xuan Fu; Lin Wang; Xin-Peng Wang; Wei-Qun Shi; Li-Yong Yuan (Chemical Engineering Journal, 2024)

Inflammation-Responsive Mesoporous Silica Nanoparticles with Synergistic Anti-inflammatory and Joint Protection Effects for Rheumatoid Arthritis Treatment - Ye-zhen Wu; Wen-yu Chen; Ying Zeng; Qi-lin Ji; Yue Yang; Xu-liang Guo; Xiu Wang (Pharmaceutical Research, 2024)

NLRP3 inflammasome activation triggers severe inflammatory liver injury in N, N-dimethylformamide-exposed mice - Xiu-Ning Zhang; Yan-Jing Zhang; Lin Wang; Shu-Jun Hong; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2024)

Characterization and sources of volatile organic compounds (VOCs) during 2022 summer ozone pollution control in Shanghai, China - Zheng Xiao; Xuerui Yang; Hongming Gu; Jialiang Hu; Tongguang Zhang; Jianian Chen; Xukang Pan; Guangli Xiu; Wei Zhang; Mingyue Lin (Atmospheric Environment, 2024)

RETRACTED ARTICLE: Micafungin exerts antitumor effect on breast cancer and osteosarcoma through preventing EMT in tumor cells in an USP7/AKT/GSK-3β pathway-dependent manner - Qian-Lin Wang; Li Wang; Qiong-Yu Li; Hui-Yin Li; Ling Lin; Dan Wei; Jin-Yun Xu; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Repair of tendons treated with peracetic acid–ethanol and gamma irradiation by EDC combined with NHS: a morphological, biochemical and biomechanical study in vitro - Rong-xing Ma; Rui-feng Li; Xiao-qiang Deng; Rui-qi Qiao; Ji-kai Li; Kun-xiu Song; Shao-lin Ji; Yong-cheng Hu (Cell and Tissue Banking, 2024)

Intestinal epithelial cells of Japanese flounder (Paralichthys olivaceus) as an in vitro model for studying intestine immune function based on transcriptome analysis - Lin Su; Baoshan Guo; Lirong Jiang; Yiping Lin; Qingyue Xu; Dong Zheng; Yunji Xiu (Fish & Shellfish Immunology, 2024)

CRISPR/Cas9-mediated knockout of Bsr-d1 enhances the blast resistance of rice in Northeast China - Ying Zhang; Xiu-Feng Lin; Li Li; Ri-Hua Piao; Songquan Wu; Anqi Song; Mengmeng Gao; Yong-Mei Jin (Plant Cell Reports, 2024)

Pruritic Erythema in a Child with Undifferentiated Connective Tissue Disease - Qi-Hao Yao; Xiu-Jiao Xia; Hui-Lin Zhi; Ze-Hu Liu (Mycopathologia, 2024)

Biochemical and Transcriptome Analysis Reveals Pigment Biosynthesis Influenced Chlorina Leaf Formation in Anoectochilus roxburghii (Wall.) Lindl - Xiu-Xian Ye; Yi-Quan Chen; Jian-She Wu; Huai-Qin Zhong; Bing Lin; Min-Ling Huang; Rong-Hui Fan (Biochemical Genetics, 2024)

Reduction of antigenicity and emulsibility improvement of ovalbumin by dielectric-barrier discharge plasma treatment induced structure modification - Pan-Pan Tang; Lin-Lin Zhang; Yu-Xin Xiong; Dan-Dan Jiang; Xiu-Bin Liu; Jun-Hu Cheng; Rana Muhammad Aadil; Zhi-Wei Liu (Innovative Food Science & Emerging Technologies, 2024)

The correct name for Gentiana albomarginata (Gentianaceae: Gentianeae) - Qi Chen; Rui-Xiu Lin; Xin-Qiang Guo (Kew Bulletin, 2024)

Establishment and characterization of an intestinal epithelial cell line from Japanese flounder (Paralichthys olivaceus) - Lin Su; Baoshan Guo; Ruixin Feng; Yunfei Pang; Jiaxue Song; Shun Zhou; Yunji Xiu (Aquaculture, 2024)

Multi-source exposure and health risks of phthalates among university students in Northeastern China - Huicheng Zhu; Na Zheng; Changcheng Chen; Ning Li; Qirui An; Wenhui Zhang; Qiuyan Lin; Zhifei Xiu; Siyu Sun; Xiaoqian Li; Yunyang Li; Sujing Wang (Science of The Total Environment, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Anti-galvanic reaction induced interfacial engineering to reconstruct ternary colloid satellite platform for exceptionally high-performance redox-responsive sensor - Mei-huang Zeng; Qiu-hong Yao; Lin-min Chen; Chen Zhang; Jing-wen Jin; Ting-Xiu Ye; Xiao-mei Chen; Zhi-Yong Guo; Xi Chen (Analytica Chimica Acta, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

4-Hydroxybenzenesulfonic acid triggers rapid preparation of phenolic aerogel composites by ambient pressure drying - Xi Zhao; Lin Chen; Peng-Gang Su; Lin-Xi Xiao; Hai-Bo Zhao; Teng Fu; Xiu-Li Wang; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

A confined self-assembly approach towards chiral photonic materials with circularly polarized structural colors for information storage and encryption - Lin-Yue Li; Dong Li; Xiu Dong; Qiang-Wu Tan; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Allyl methyl disulfide (AMDS) prevents N,N-dimethyl formamide-induced liver damage by suppressing oxidative stress and NLRP3 inflammasome activation - Long-Xia Li; Lin Wang; Shuo Wang; Xiu-Ning Zhang; Hong Liu; Yan-Jing Zhang; Chuan-Tao Wu; Cui-Li Zhang; Tao Zeng (Food and Chemical Toxicology, 2023)

Joint effects of prenatal exposure to air pollution and pregnancy-related anxiety on birth weight: A prospective birth cohort study in Ma’anshan, China - Zhen-Hua Li; Yi-Cheng Mao; Yang Li; Sun Zhang; Hui-Yu Hu; Zhe-Ye Liu; Xue-Jie Liu; Jia-Wen Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Research, 2023)

Comparison of demineralized bone matrix with different cycling crushing times in posterolateral fusion model of athymic rats - Shao-Lin Ji; Xiao-Dan Zhao; Li-Min Wang; Cheng-Gang Pang; Wen-Jing Li; Kun-Xiu Song; Rong-Xing Ma; Rui-Feng Li; Jing-Yu Zhang; Yong-Cheng Hu (Cell and Tissue Banking, 2023)

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

Emissions from international airport and its impact on air quality: A case study of beijing daxing international airport (PKX), China - Ya-nan Wang; Chao Zou; Tian-ge Fang; Nai-xiu Sun; Xiao-yu Liang; Lin Wu; Hong-jun Mao (Environmental Pollution, 2023)

Evaporative emission characteristics of VOCs from in-use light-duty gasoline vehicles - Teng Zi; Pengrui Wang; Baoxian Liu; Ying Zhou; Xiu'e Shen; Lin Zhang; Yang Lu; Qian Feng; Yanyan Yang; Jianlei Lang (Atmospheric Environment, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Low-protein diet promotes nitrogen retention efficiency via enhanced renal urea reabsorption and microbial hydrogen incorporation in the rumen of goats - Xiu Min Zhang; Wen Xun Chen; Qiong Xian Yan; Chao Wang; Bo Lin; Si Yu Yi; Rong Wang; Zhi Yuan Ma; Qiu Shuang Li; Arjan Jonker; Xue Zhao Sun; Suntorn Wittayakun; et al. (Animal Feed Science and Technology, 2023)

Coupled effects of pH and kaolinite colloids on antibiotic transport in porous media - Shuhua JI; Xiaowen LIU; Xiu MENG; Shaohui XU; Qing LIN (Pedosphere, 2023)

Corrigendum to “Using Fe biofortification strategies to reduce both Ni concentration and oral bioavailability for rice with high Ni” [J Hazard Mater 452 (2023) 131367] - Xin-Ying Lin; Jia-Hui Liang; Duo-Duo Jiao; Jun-Xiu Chen; Ning Wang; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Successful Treatment of Diffuse Pustular Inflammatory Tinea Capitis in the Elderly with Repeated Debridement, Oral Terbinafine and Short-Course Steroids - Yuan Xu; Xiu-Jiao Xia; Hui-Lin Zhi; Ze-Hu Liu (Mycopathologia, 2023)

Trichoscopy for early diagnosis and follow-up of pet-related neonatal tinea capitis - Hui-Lin Zhi; Xiu-Jiao Xia; Hong Shen; Wen-Wen Lv; Yan Zhong; Bo Sang; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2023)

Pregnane steroid glycosides with multidrug resistance reversal activity from the stems of Marsdenia tenacissima - Xiu-Qing Song; Lin-Lin Tian; Tao Ye; Hu Liu; Hua Zhang (Phytochemistry, 2023)

β-Cyclodextrin network crosslinked by novel phosphonium-based tetrakiscarboxylic acid derived from PH3 tail gas: Synthesis and application for rapid removal of organic dyes from wastewater - Yu-Lin Hong; Jian Sun; Xiu-Qin Fang; Qing-Wen Liu; Chang Wang; Cheng-Mei Liu (Carbohydrate Polymers, 2023)

Development of a chiral electrochemical sensor based on copper–amino acid mercaptide nanorods for enantioselective discrimination of tryptophan enantiomers - Qian-xiu Pan; Yun-cong Yang; Ning-ning Zhao; Baogang Zhang; Lin Cui; Chun-yang Zhang (Analytica Chimica Acta, 2023)

First report of Pestalotiopsis neolitseae causing leaf blight on Photinia × fraseri in China - Xiu-Lan Xu; Si-Yi Liu; Qian-Gang Xiao; Yi-Cong Lv; Ying-Gao Liu; Chun-Lin Yang (Journal of Plant Pathology, 2023)

Mid-Neoproterozoic tectonic switch from orogeny to intraplate extension in NW Tarim Craton: New evidence from a composite dike of the Aksu Group - Hong-Xiang Wu; Feng-Qi Zhang; Yildirim Dilek; Han-Lin Chen; Kong-Yang Zhu; Xiu-Bin Lin; Qin-Yan Wang; Hong-Dan Deng; Xiao-Gan Cheng (Precambrian Research, 2023)

Efficacy of bivalent vaccine against Aeromonas salmonicida and Edwardsiella tarda infections in turbot - Lin Su; Huimin Guo; Baoshan Guo; Jingyuan Yi; Zongrui Yang; Shun Zhou; Yunji Xiu (Fish & Shellfish Immunology, 2023)

Enhanced vitamin K2 production by engineered Bacillus subtilis during leakage fermentation - Meng-jie Zhou; Jing Wu; Liu-xiu Hu; Wen-song Hu; Jun-bao Huang; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Zheng-lian Xue; Yan Liu (World Journal of Microbiology and Biotechnology, 2023)

Immuno-Protective Efficiency of the Bivalent Inactivated Vaccine Against Vibrio scophthalmi and Aeromonas salmonicida Infections in Turbot (Scophthalmus maximus L.) - Shun Zhou; Xujia Zheng; Yuanyuan Ding; Lin Su; Qing Huang; Yunji Xiu (Journal of Ocean University of China, 2023)

A novel fluorescent probe for imaging endogenous hydrogen sulfide in living cells and mice models of acute liver injury - Kai Wang; Rui Guo; Xu-Yang Chen; Xiu-Lin Li; Zhi-Gang Hu; Xiao Wang; Chao-Yue Wang; Ya-Juan Qin; Kun Yao; Yu-Shun Yang (Chemical Engineering Journal, 2023)

Preparation of micro-fibrillated cellulose fibers by a simple two-step refining process for paper- based flexible electronic devices - Chenglong Fu; Changmei Lin; Weipeng Zhang; Yaling Lin; Jinhong Xiu; Yonghao Ni; Liulian Huang (Chemical Engineering Journal, 2023)

Using Fe biofortification strategies to reduce both Ni concentration and oral bioavailability for rice with high Ni - Xin-Ying Lin; Jia-Hui Liang; Duo-Duo Jiao; Jun-Xiu Chen; Ning Wang; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Transcriptome Analysis Reveals the Regulation Role of miR-144-5p in Intestinal Immunity of Japanese Flounder (Paralichthys olivaceus) - Yingrui Li; Lin Su; Baoshan Guo; Kefeng Xu; Shun Zhou; Yunji Xiu (Journal of Ocean University of China, 2023)

A new chamigrane sesquiterpene from the rice fermentation of Antrodiella albocinnamomea - Min Guo; Ying-Zhong Liang; Xiu-Ming Cui; Lin-Jiao Shao; Yin-Fei Li; Xiao-Yan Yang (Natural Product Research, 2023)

Identification of sea bass freshness grades using laser-induced breakdown spectroscopy coupled with multivariable analysis - Zilin Yue; Hong Lin; Xiu Fang; Ye Tian; Wenqian Yan; Jiayi Yao; Xiaohui Chen; Kaiqiang Wang (Food Control, 2023)

Seafood allergy: Allergen, epitope mapping and immunotherapy strategy - Ziye Zhang; Xiu-Min Li; Hao Wang; Hong Lin; Hang Xiao; Zhenxing Li (Critical Reviews in Food Science and Nutrition, 2023)

The ginsenoside Rh2 protects porcine oocytes against aging and oxidative stress by regulating SIRT1 expression and mitochondrial activity - Hongye Liu; Zhi-Yong An; Zhou-Yan Li; Liu-Hui Yang; Xiu-Li Zhang; Yan-Tong Lv; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2023)

Responses of microbial community to geochemical parameters on vertical depth in bioheap system of low-grade copper sulfide - Xiu-Tong Li; Zhong-Sheng Huang; Ye Huang; Zhen Jiang; Zong-Lin Liang; Hua-Qun Yin; Guang-Ji Zhang; Yan Jia; Ye Deng; Shuang-Jiang Liu; Cheng-Ying Jiang (Science of The Total Environment, 2023)

Natural Polyphenol-Inspired Polymer towards Multifunction and High Performance - Guan-Qi Zheng; Bo-Wen Liu; Ling Yuan; Lin Chen; Xiu-Li Wang; Hai-Bo Zhao; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Valorizing kitchen waste to produce value-added fertilizer by thermophilic semi-continuous composting followed by static stacking: Performance and bacterial community succession analysis - Xiang-Yu Peng; Shi-Peng Wang; Xiu-Lin Chu; Zhao-Yong Sun; Zi-Yuan Xia; Cai-Yun Xie; Min Gou; Yue-Qin Tang (Bioresource Technology, 2023)

Insight into the conformational and allergenicity alterations of shrimp tropomyosin induced by Sargassum fusiforme polyphenol - Yiming Zhao; Ziye Zhang; Zhenxing Li; Xiu-Min Li; Hao Wang; Hong Lin (Food Research International, 2023)

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Sequential combination of pre-chlorination and powdered activated carbon adsorption on iodine removal and I-THMs control in drinking water - Renjie Pan; Yi-Li Lin; Tian-Yang Zhang; Xiu-Li Wei; Zheng-Yu Dong; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Chemosphere, 2023)

Bacterial induced miR-144-5p modulates intestinal inflammatory response of Japanese flounder by targeting Hsp90α-dependent NLR signaling pathway - Yingrui Li; Lin Su; Baoshan Guo; Shun Zhou; Chao Li; Yunji Xiu (Aquaculture, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

A glyoxylate-containing benzene derivative and butenolides from a marine algicolous fungus Aspergillus sp. SCSIO 41304 - Xin Qi; Wei-Hao Chen; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Yong-Hong Liu; Jun-Feng Wang; Yong Li (Natural Product Research, 2023)

Gastropod chemoreception behaviors—Mechanisms underlying the perception and location of targets and implications for shellfish fishery development in aquatic environments - Zheng-Lin Yu; Mei-Jie Yang; Hao Song; Tao Zhang; Xiu-Tang Yuan (Frontiers in Marine Science, 2023)
Chemoreception is one of the most important senses and it plays a key role in the survival and adaptation of animals to their environments. Many gastropods, such as Rapana venosa and Neptunea cumingii , have emerged as economically important shellfish. Meanwhile, invasive gastropods have destroyed commercial shellfisheries in many countries. Given the importance of chemoreception in the behavior of aquatic gastropods, the mechanism of their chemical perception has recently garnered attention. To provide a foundation for understanding the chemoreception of aquatic gastropods, we reviewed recent studies and summarized the chemoreception behaviors and mechanisms that gastropods use to perceive and locate targets in aquatic environments, along with relevant molecular and genetic insights. We highlight several of the implications of these studies for chemoreception-related research and shellfish fishery development. This review should aid in the rational development and utilization of gastropod resources as well as in controlling the populations of invasive species.

Seismic Multiple Attenuation in the Continent–Ocean Transition Zone of the Northern South China Sea - Nan Chen; Chun-Feng Li; Yong-Lin Wen; Peng Wang; Xiu-Lian Zhao; Xiao-Li Wan (Journal of Marine Science and Engineering, 2023)
In this study, we process four new multichannel reflection seismic profiles acquired in 2015 and 2016 in the continent–ocean transition zone (COT) of the northern South China Sea (SCS). We apply a multi-domain, progressive, and seabed-controlled denoising technique and obtain a good denoising effect. Combining velocity analysis in the multi-round time domain and forward modeling, we analyze the types and characteristics of multiples in the study area and formulate an effective demultiple technique to attenuate strong seabed multiples, diffracted multiples from rough seafloor, and other multiples from deep reflectors. The processing results show that the sea surface-related multiple elimination technique predicts the sea surface-related multiples accurately by data convolution, and has a good effect in attenuating seabed multiples. Diffracted multiple attenuation method extracts high-frequency and high-energy diffracted multiples, and suppresses multiples by the energy ratios of multiples to primary events. To attenuate deep multiples, we select predictive deconvolution to attenuate periodic deep multiples after many trials and detailed analysis. The combination of these different techniques in sequence proves to be quite effective in attenuating different seismic multiples in the COT. The imaged crustal structures near the COT often show strong magmatism and/or basement uplifting. The faulted and thinned continental crust adjacent to the COT corresponds to the lowest free-air gravity anomalies. Gravity anomalies often increase from the COT to the oceanic crust. An exception is to the northeast of the SCS, where the relatively wide COT shows very high gravity anomalies, likely induced by mantle upwelling and serpentinization.

SERS detection of thiram using polyacrylamide hydrogel-enclosed gold nanoparticle aggregates - Kaiqiang Wang; Zilin Yue; Xiu Fang; Hong Lin; Lei Wang; Limin Cao; Jianxin Sui; Lei Ju (Science of The Total Environment, 2023)

Steroid glycosides from the roots of Marsdenia tenacissima - Xiu-Qing Song; Lin-Lin Tian; Tao Ye; Hu Liu; Hua Zhang (Phytochemistry, 2023)

Spectrum and mortality of opportunistic infections among HIV/AIDS patients in southwestern China - Sirun Meng; Qiao Tang; Zhiman Xie; Nianning Wu; Yingmei Qin; Rongfeng Chen; Xiaoyu Chen; Xiu Chen; Yueqi Li; Minjuan Shi; Li Ye; Hao Liang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
We describe the opportunistic infections (OIs) of HIV/AIDS to understand the spectrum, mortality, and frequency of multiple coinfected OIs among HIV/AIDS patients in southern China, where OIs are severe. We carried out a retrospective cohort study of hospitalized HIV-infected individuals at the Fourth People’s Hospital of Nanning, Guangxi, China, from Jan. 2011 to May. 2019. The chi-square test was used to analyze cross-infection; the Kaplan‒Meier analysis was used to compare mortality. A total of 12,612 HIV-infected patients were admitted to this cohort study. Among them, 8982 (71.2%) developed one or more OIs. The overall in-hospital mortality rate was 9.0%. Among the patients, 35.6% coinfected one OI, and 64.4% coinfected more than two OIs simultaneously. Almost half of the patients (60.6%) had CD4 + T-cell counts < 200 cells/μL. Pneumonia (39.8%), tuberculosis (35.3%), and candidiasis (28.8%) were the most common OIs. Coinfected cryptococcal meningitis and dermatitis are the most common combined OIs. The rate of anaemia (17.0%) was highest among those common HIV-associated complications. Multiple OIs are commonly found in hospitalized HIV/AIDS patients in southwestern China, which highlights the need for improved diagnosis and treatment.

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Development of Two Recombinase Polymerase Amplification EXO (RPA-EXO) and Lateral Flow Dipstick (RPA-LFD) Techniques for the Rapid Visual Detection of Aeromonas salmonicida - Shun Zhou; Xujia Zheng; Zongrui Yang; Qing Huang; Jingyuan Yi; Lin Su; Baoshan Guo; Yunji Xiu (Marine Biotechnology, 2022)

Effects of high-temperature stress on photosynthesis of a new variety "SF-2" in Neoporphyra haitanensis - Xiu-Wen Yang; Lin-Bin Huang; Xing-Hong Yan (Journal of Applied Phycology, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

First report of leaf blight on Panax notoginseng caused by Pestalotiopsis trachycarpicola in China - Cheng Zhong Lan; Xiong Lin; Yu Li Dai; Lin Gan; Xiao Fei Liu; Hong Chun Ruan; Xiu Juan Yang (Journal of Plant Pathology, 2022)

First record of Ulva californica in the mainland of China: a single alien parthenogenetic population in discontinuous distribution - Xiu Wei; Wenzheng Liu; Xuyin Lin; Qianchun Liu; Peng Jiang (Journal of Oceanology and Limnology, 2022)

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

Immune responses to Vibrio vulnificus formalin‐killed vaccine and ghost vaccine in Scophthalmus maximus - Shun Zhou; Ying Li; Jingyuan Yi; Xujia Zheng; Qing Huang; Lin Su; Baoshan Guo; Zongrui Yang; Yunji Xiu (Journal of Fish Diseases, 2022)
In this research, Vibrio vulnificus formalin‐killed (FKCs) vaccine and ghost (VVGs) vaccine were successfully developed, and shown to prevent vibriosis of Scophthalmus maximus resulting from V. vulnificus. The antibody titre of FKCs and VVGs vaccine was 1: 2 8 and 1: 2 11 . The RPS of FKCs and VVGs vaccine was 60% and 80%. In order to improve the understanding of vaccine protection mechanism, transcriptome data was used to analyse the immune response of S. maximus infected with V. vulnificus after vaccination with FKCs and VVGs vaccine. In the SmCon and SmIV groups, a series of innate immune‐related genes were upregulated (such as, TLR5, Tp12, AP‐1 and IL‐1β) or downregulated (such as, CASP6 and CASP8), which suggested that the immune protection mechanism induced by inactivated vaccine was similar to that of autoimmune response. In the SmIV and SmGho group, a number of innate and adaptive immune‐related genes (such as, STAT1, IFN‐γ and MHC Ia) were activated, in which the expression of these genes was higher in SmGho, and VVGs vaccine induced stronger innate and acquired immune responses. In conclusion, the results lay a foundation for further study on the molecular mechanisms of immune protection induced by VVGs vaccine and FKCs vaccine.

Modelling the influence of submesoscale processes on phytoplankton dynamics in the northern South China Sea - Peng Xiu; Lin Guo; Wentao Ma (Frontiers in Marine Science, 2022)
Submesoscale processes in the ocean vary rapidly in both space and time, and are often difficult to capture by field observations. Their dynamical connection with marine biology remains largely unknown because of the intrinsic link between temporal and spatial variations. In May 2015, satellite chlorophyll data demonstrated high concentration patches in the edge region between mesoscale eddies, which were higher than those in the cyclonic eddy core region in the northern South China Sea (NSCS). The underlying mechanisms were examined with a high-resolution physical-biological model. By tracking Lagrangian particles in the model, this study shows that the edge region between eddies is a submesoscale frontal region that is prone to intense upwelling and downwelling motions. We identified two key submesoscale mechanisms that affect nutrient transport flux significantly, submesoscale fontal dynamics and submesoscale coherent eddies. The dynamics associated with these two mechanisms were shown to be able to inject subsurface nutrients into the upper layer, generate the high chlorophyll patch, and alter phytoplankton community structure in the NSCS. This study shows the importance of submesoscale processes on phytoplankton dynamics in the NSCS and highlights the need for high-resolution observations.

Effects of U on the growth, reactive oxygen metabolism and osmotic regulation in radish (Raphanus sativus L.) - Guo Wu; Xi Chen; Ting Zheng; Pi-xian Xiao; Ning-ying Zhong; Xiu-lin Yang; Yi Li; Wei Li (Environmental Science and Pollution Research, 2022)

Bedside Diagnosis for Disseminated Deep Dermatophytosis: a Case Series Study - Xiu-Jiao Xia; Hong Shen; Hui-Lin Zhi; Yan Zhong; Bo Sang; Wen-Wen Lv; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2022)

Effects of conservation measures on crop diversity and their implications for climate-resilient livelihoods: the case of Rupa Lake Watershed in Nepal - Yun-li Bai; Chao Fu; Balaram Thapa; Ram Balladur Rana; Lin-xiu Zhang (Journal of Mountain Science, 2022)
Agrobiodiversity conservation is vital for achieving sustainability, but empirical studies on the effects of different practices or measures on crop diversity are rare. This study aims to estimate the effects of raising conservation awareness (RCA), building diversity blocks (BDB), and their combination on crop diversity among 240 randomly selected households surrounding the Rupa Lake Watershed in Nepal. Based on descriptive analysis and multiple regression models, the results indicate that the two single measures had no significant effect on the numbers of crop species and varieties grown by households in 2018. However, the combination of RCA and BDB had a significantly positive effect on the number of crop varieties, especially for grain and vegetable crops. Considering that these crops are essential in the daily lives of local people, the results indicate that a strategy that combines both awareness raising and on-farm conservation measures can generate higher crop diversity and better serve the climate-resilient livelihoods of people in mountainous areas.

Sphingobacterium bovistauri sp. nov., Isolated from the Faeces of Bos Taurus - Qiong Wang; Zhi-Qin Fang; Chen-Lu Zhang; Jian-Qiang Shen; Jian-Dong Lai; Xiu-Lin Han; Tao Lu (Current Microbiology, 2022)

Genomic characterization of a new enamovirus infecting common bean - Ruo-bin Lu; Ping-xiu Lan; Ru-jing Kang; Guan-lin Tan; Xiao-jiao Chen; Ruhui Li; Fan Li (Archives of Virology, 2022)

Description of Aureibaculum luteum sp. nov. and Aureibaculum flavum sp. nov. isolated from Antarctic intertidal sediments - Xiao-yan He; Ning-hua Liu; Chao-yi Lin; Mei-ling Sun; Xiu-lan Chen; Yu-zhong Zhang; Yu-qiang Zhang; Xi-ying Zhang (Antonie van Leeuwenhoek, 2022)

Synthesis, antifungal activity and 3D-QSAR study of novel acyl thiourea compounds containing gem-dimethylcyclopropane ring - Mei Huang; Min Huang; Xiu Wang; Wen-Gui Duan; Gui-Shan Lin; Fu-Hou Lei (Molecular Diversity, 2022)

Advenella mandrilli sp. nov., a bacterium isolated from the faeces of Mandrillus sphinx - Qiong Wang; Xiu-Lin Han; Zhi-Qin Fang; Chen-Lu Zhang; Chun Li; Tao Lu (Antonie van Leeuwenhoek, 2022)

Ethylene insensitive mutation alleviates cadmium-induced photosynthesis impairment in Arabidopsis plants - Qi-Yu Zhao; Chun-Xiu Gu; Yu Wang; Guang-Zhe Li; Lin Hao (Acta Physiologiae Plantarum, 2022)

Antioxidant CPA-type indole alkaloids produced from the deep-sea derived fungus Aspergillus sp. SCSIO 41024 - Wei-Hao Chen; Kun-Long Li; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Jun-Jian Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2021)

Sphingobacterium rhinopitheci sp. Nov., isolated from the faeces of Rhinopithecus bieti in China - Xiu-Lin Han; Qiong Wang; Chen-Lu Zhang; Zhi-Qin Fang; Jian-Qiang Shen; Song Huang; Tao Lu (Archives of Microbiology, 2021)

Flavobacterium difficile sp. nov., isolated from a freshwater waterfall - Wen-Ming Chen; Ya-Xiu You; Chiu-Chung Young; Shih-Yao Lin; Shih-Yi Sheu (Archives of Microbiology, 2021)

Evaluation of the RNA extraction methods in different Ginkgo biloba L. tissues - Xiao-lin Zhang; Xiao-li Huang; Jia Li; Mei Mei; Wan-qi Zeng; Xiu-jun Lu (Biologia, 2021)

Prenylated xanthones and biphenyls from Garcinia esculenta with antistaphylococcal activity - Dan Zheng; Hong Zhang; Jia-Ming Jiang; Yu-Yu Chen; Shi-Jie Wan; Zhi-Xiu Lin; Hong-Xi Xu (Natural Product Research, 2021)

Identification of a delayed leaf greening gene from a mutation of pummelo - Hui-Wen Yu; Zhi-Hao Lu; Xia Wang; Dan Liu; Jia-Xian He; Xiao-Lin Jiang; Ling-Jun Ke; Wen-Wu Guo; Xiu-Xin Deng; Qiang Xu (Science China Life Sciences, 2021)

Effects of Fish Oil Combined with Selenium and Zinc on Learning and Memory Impairment in Aging Mice and Amyloid Precursor Protein Processing - Chao-xu Fu; Lin Dai; Xiu-yuan Yuan; Yan-ji Xu (Biological Trace Element Research, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Carbon isotope variations of modern soils in the eastern margin of the Tibetan Plateau and their controlling factors - Lin Qi; Yan-song Qiao; Zong-xiu Liu; Sha-sha Peng; Yu Cheng; Yan Wang; Xu-jiao Zhang; Ming-zhong Tian; Shuai-bin Yang; Wen-bin Bai (Journal of Mountain Science, 2021)

Spatial Mismatch or Not? Evidence from Public Janitors in Xi’an, China - Chen Chen; Lin Cheng; Chunliang Xiu; Jiuquan Li (Chinese Geographical Science, 2021)

Soil anti-scourability enhanced by herbaceous species roots in a reservoir water level fluctuation zone - Wen-xiu Xu; Ling Yang; Yu-hai Bao; Jin-lin Li; Jie Wei (Journal of Mountain Science, 2021)

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Mitigating Climate Change for Sugarcane Improvement: Role of Silicon in Alleviating Abiotic Stresses - Krishan K. Verma; Pratiksha Singh; Xiu-Peng Song; Mukesh Kumar Malviya; Rajesh Kumar Singh; Gan-Lin Chen; Sushil Solomon; Yang-Rui Li (Sugar Tech, 2020)

Cloning and Characterization of a Ginsenoside-Hydrolyzing α-L-Arabinofuranosidase, CaAraf51, From Cellulosimicrobium aquatile Lyp51 - Sha-Sha Zuo; Yu-Chen Wang; Ling Zhu; Jiang-Yuan Zhao; Ming-Gang Li; Xiu-Lin Han; Meng-Liang Wen (Current Microbiology, 2020)

RES transformation for biosynthesis and detoxification - Jin-Quan Huang; Jia-Ling Lin; Xiao-Xiang Guo; Xiu Tian; Ye Tian; Xiao-Xia Shangguan; Ling-Jian Wang; Xin Fang; Xiao-Ya Chen (Science China Life Sciences, 2020)

Genome-wide identification of the Sec-dependent secretory protease genes in Erwinia amylovora and analysis of their expression during infection of immature pear fruit - Wang-bin Zhang; Hai-lin Yan; Zong-cai Zhu; Chao Zhang; Pei-xiu Du; Wen-jun Zhao; Wei-min Li (Journal of Zhejiang University-SCIENCE B, 2020)

Alfalfa MsCBL4 enhances calcium metabolism but not sodium transport in transgenic tobacco under salt and saline–alkali stress - Yimin An; Xiao-Xue Yang; Lishuang Zhang; Jun Zhang; Binghao Du; Lin Yao; Xiu-ting Li; Changhong Guo (Plant Cell Reports, 2020)

Cinnamaldehyde improves the growth performance and digestion and absorption capacity in grass carp (Ctenopharyngodon idella) - Yang Zhou; Wei-Dan Jiang; Jin-Xiu Zhang; Lin Feng; Pei Wu; Yang Liu; Jun Jiang; Sheng-Yao Kuang; Ling Tang; Yan Peng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2020)

Gastric smooth muscle cells manifest an abnormal phenotype in Parkinson’s disease rats with gastric dysmotility - Xiao-Lin Xiu; Li-Fei Zheng; Xiao-Yu Liu; Yan-Yan Fan; Jin-Xia Zhu (Cell and Tissue Research, 2020)

Gelsemine, a natural alkaloid extracted from Gelsemium elegans Benth. alleviates neuroinflammation and cognitive impairments in Aβ oligomer-treated mice - Liping Chen; Hanbo Pan; Yujing Bai; Huiqin Li; Wen Yang; Zhi-Xiu Lin; Wei Cui; Yan-Fang Xian (Psychopharmacology, 2020)

Release from below- and aboveground natural enemies contributes to invasion success of a temperate invader - Yuan-Zheng Zhao; Ming-Chao Liu; Yu-Long Feng; Dong Wang; Wei-Wei Feng; Keith Clay; Lekeah A. Durden; Xiu-Rong Lu; Shuo Wang; Xiao-Lin Wei; De-Liang Kong (Plant and Soil, 2020)

Expression of the subgroup IIIf bHLH transcription factor CpbHLH1 from Chimonanthus praecox (L.) in transgenic model plants inhibits anthocyanin accumulation - Rong Zhao; Xiaoxi Song; Nan Yang; Longqing Chen; Lin Xiang; Xiu-Qun Liu; Kaige Zhao (Plant Cell Reports, 2020)

Two new aromatic polyketides from a deep-sea fungus Penicillium sp. SCSIO 06720 - Cui Guo; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Xian-Wen Yang; Xin-Peng Tian; Jun-Feng Wang; Yong-Hong Liu (Natural Product Research, 2020)

First report of Fusarium oxysporum f. sp. canariensis causing Fusarium wilt on Canary Island date palm (Phoenix canariensis Hort. Ex Chabaud) in China - Cheng Zhong Lan; Yu Li Dai; Lin Gan; Jin Ai Yao; Xiu Juan Yang (Journal of Plant Pathology, 2020)

Two new phenolic glycosides from the seeds of Citrullus lanatus - Xiao-Qian Zhang; Jing Shi; Shi-Xiu Feng; Lin Xue; Li-Ping Tian (Natural Product Research, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Complexin I knockout rats exhibit a complex neurobehavioral phenotype including profound ataxia and marked deficits in lifespan - Yang Xu; Xiao-Ming Zhao; Jia Liu; Yang-Yang Wang; Liu-Lin Xiong; Xiu-Ying He; Ting-Hua Wang (Pflügers Archiv - European Journal of Physiology, 2020)

Origins of Beta Amyloid Differ Between Vascular Amyloid Deposition and Parenchymal Amyloid Plaques in the Spinal Cord of a Mouse Model of Alzheimer’s Disease - Qiuju Yuan; Xiaodong Liu; Yan-Fang Xian; Ying Tang; Juntao Zou; Xie Zhang; Pengyun Huang; Wutian Wu; You-qiang Song; Zhi-Xiu Lin (Molecular Neurobiology, 2020)

Biogeochemical responses of soil ecosystems to raw coal pollution in Xuanhua, China - Yu Liu; Wu Xiang; Jie Zhu; Xiu-Zhi Zhang; Xu-Dong Xing; Wei-Lin Yang (Journal of Soils and Sediments, 2020)

Cloning and Expression Analysis of the ScD53 Gene from Sugarcane - Ai-Li Lv; Xu-Juan Li; Chun-Jia Li; Hong-Bo Liu; Qiu-Yan Zi; Xiu-Qin Lin; Xin-Long Liu (Sugar Tech, 2019)

Rapamycin attenuates Tc1 and Tc17 cell responses in cigarette smoke-induced emphysema in mice - Hui Zhang; Xiu Zhou; Xin Chen; Yuanzhen Lin; Shilin Qiu; Yun Zhao; Qiya Tang; Yi Liang; Xiaoning Zhong (Inflammation Research, 2019)

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

Fractal characterization of sediment particle size distribution in the water-level fluctuation zone of the Three Gorges Reservoir, China - Jin-lin Li; Yu-hai Bao; Jie Wei; Xiu-bin He; Qiang Tang; Jean de Dieu Nambajimana (Journal of Mountain Science, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

The LRP6 functional mutation rs2302685 contributes to individual susceptibility to alcoholic liver injury related to the Wnt/β-catenin-TCF1-CYP2E1 signaling pathway - Ying Xu; Dan Chen; Xiu-Xian Lin; Qing Zhao; Jing Guo; Li-jie Chen; Wei Zhang; Jian Xiao; Guang-Hui Lian; Shi-Fang Peng; Dong Guo; Hong Yang; et al. (Archives of Toxicology, 2019)

NMDA Receptor Antagonist MK801 Protects Against 1-Bromopropane-Induced Cognitive Dysfunction - Lin Xu; Xiaofei Qiu; Shuo Wang; Qingshan Wang; Xiu-Lan Zhao (Neuroscience Bulletin, 2019)

The spatial–temporal dynamics of bamboo aphid dispersal flight along with their natural enemies: biocontrol implication - Kai Guo; Haipin Lin; Xiu Su; Jianghong Wang; Cristian Montalva; Shengyu Shao; Xiang Zhou (Agroforestry Systems, 2019)

OsDCL3b affects grain yield and quality in rice - Peng-Fei Liao; Jie-Xiu Ouyang; Jian-Jun Zhang; Lan Yang; Xin Wang; Xiao-Jue Peng; Dong Wang; You-Lin Zhu; Shao-Bo Li (Plant Molecular Biology, 2019)

A new cyclohexenone from the tin mine tailings-derived fungus Aspergillus flavus YIM DT 10012 - Wei-Xun Chunyu; Jiang-Yuan Zhao; Zhang-Gui Ding; Xiu-Lin Han; Yong-Xia Wang; Jian-Hai Ding; Fei Wang; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2019)

Ginsenoside Compound K Regulates Amyloid β via the Nrf2/Keap1 Signaling Pathway in Mice with Scopolamine Hydrobromide-Induced Memory Impairments - Qing Yang; Jianan Lin; Huiyuan Zhang; Yingna Liu; Mo Kan; Zhiru Xiu; Xijun Chen; Xingcheng Lan; Xiaohua Li; Xiaozheng Shi; Na Li; Xiaobo Qu (Journal of Molecular Neuroscience, 2019)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Induction and identification of tetraploid Hedychium coronarium through thin cell layer culture - Hong-Yan Tu; Ai-Ling Zhang; Wang Xiao; Ya-Rou Lin; Jun-Hui Shi; Yong-Wei Wu; Si-Tong Wu; Chun-Hui Zhong; Shui-Xiu Mo (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Offspring sex ratio and reproductive tactics of Leptocybe invasa (Hymenoptera: Eulophidae): testing the effect of environmental characteristics - Xia-Lin Zheng; Kai Lin; Zong-You Huang; Jun Li; Zhen-De Yang; Xiu-Hao Yang; Wen Lu (International Journal of Tropical Insect Science, 2018)

A factor analysis of landscape metrics of particles deposited on leaf surface - Lin Lin; Guojian Chen; Jingli Yan; Rongli Tang; Xiu Yuan; Zhe Yin; Rui Zhang (Environmental Science and Pollution Research, 2018)

New podolactones from the seeds of Podocarpus nagi and their anti-inflammatory effect - Zhe-Ling Feng; Tian Zhang; Jing-Xin Liu; Xiu-Ping Chen; Li-She Gan; Yang Ye; Li-Gen Lin (Journal of Natural Medicines, 2018)

Integrating CNVs into meta-QTL identified GBP4 as positional candidate for adult cattle stature - Xiu-Kai Cao; Yong-Zhen Huang; Yi-Lei Ma; Jie Cheng; Zhen-Xian Qu; Yun Ma; Yue-Yu Bai; Feng Tian; Feng-Peng Lin; Yu-Lin Ma; Hong Chen (Functional & Integrative Genomics, 2018)

Biotransformation of ursolic acid by Alternaria longipes AS3.2875 - Chen-Xi Zhang; Wei-Jun Ma; Dai-Lin Liu; Xiu-Juan Jia; Yan-Min Zhao (Natural Product Research, 2018)

The Distal Gut Bacterial Community of Some Primates and Carnivora - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Li Han; Yi Jiang; Xue-Shi Huang; Cheng-Lin Jiang (Current Microbiology, 2018)

α-Glucosidase inhibitors and phytotoxins from Streptomyces xanthophaeus - Jing Wei; Xiu-Yun Zhang; Shan Deng; Lin Cao; Quan-Hong Xue; Jin-Ming Gao (Natural Product Research, 2017)

Two new diketopiperazines from the tin mine tailings-derived fungus Schizophyllum commune YIM DT 10058 - Wei-Xun Chunyu; Zhang-Gui Ding; Jiang-Yuan Zhao; Yong-Xia Wang; Xiu-Lin Han; Ming-Gang Li; Meng-Liang Wen (Natural Product Research, 2017)

Grape hexokinases are involved in the expression regulation of sucrose synthase- and cell wall invertase-encoding genes by glucose and ABA - Xiu-Qin Wang; Li-Li Zheng; Hao Lin; Fei Yu; Li-Hui Sun; Li-Mei Li (Plant Molecular Biology, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Enterovirga rhinocerotis gen. nov., sp. nov., isolated from Rhinoceros unicornis faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Hui Lei; Yi Jiang; Li Han; Xue-Shi Huang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

Joint 3D traveltime calculation based on fast marching method and wavefront construction - Hui Sun; Jian-Guo Sun; Zhang-Qing Sun; Fu-Xing Han; Zhi-Qiang Liu; Ming-Chen Liu; Zheng-Hui Gao; Xiu-Lin Shi (Applied Geophysics, 2017)

Variation in carbohydrates and screening of related differential proteins during the seed germination of Magnolia sieboldii K. Koch - Mei Mei; Xiu-jun Lu; Xiao-lin Zhang; Guang-lin Liu; Xiao-mei Sun (Trees, 2017)

Iridoid glycosides from Callicarpa nudiflora Hook - Shi-Xiu Feng; Bo Yi; Min Zhang; Jing Xu; Hai Lin; Wen-Tong Xu (Natural Product Research, 2017)

HuR mediates motility of human bone marrow-derived mesenchymal stem cells triggered by sphingosine 1-phosphate in liver fibrosis - Na Chang; Jingjing Ge; Lei Xiu; Zhongxin Zhao; Xianghui Duan; Lei Tian; Jieshi Xie; Lin Yang; Liying Li (Journal of Molecular Medicine, 2017)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Microbacterium gilvum sp. nov., isolated from civet faeces - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Yi Jiang; Li Han; Cheng-Lin Jiang; Xue-Shi Huang (Antonie van Leeuwenhoek, 2016)

Suppression of dioxins by S-N inhibitors in pilot-scale experiments - Ming-Xiu Zhan; Jian-Ying Fu; Tong Chen; Xiao-Qing Lin; Xiao-Dong Li; Jian-Hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Anisotropic Drained Deformation Behavior and Shear Strength of Natural Soft Marine Clay - Yu-Ke Wang; Lin Guo; Yu-Feng Gao; Yue Qiu; Xiu-Qing Hu; Ying Zhang (Marine Georesources & Geotechnology, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Metabolomic analysis of competent larvae and juvenile veined rapa whelks (Rapana venosa) - Hao Song; Li-Yuan Sun; Zheng-Lin Yu; Li-Na Sun; Dong-Xiu Xue; Tao Zhang; Hai-Yan Wang (Marine Biology, 2016)

Emission and distribution of PCDD/Fs and CBzs from two co-processing RDF cement plants in China - Tong Chen; Ming-Xiu Zhan; Xiao-qing Lin; Ye-qing Li; Jiang Zhang; Xiao-Dong Li; Jian-hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Occurrence, spatial distribution, sources, and risks of polychlorinated biphenyls and heavy metals in surface sediments from a large eutrophic Chinese lake (Lake Chaohu) - Wei He; Ze-Lin Bai; Wen-Xiu Liu; Xiang-Zhen Kong; Bin Yang; Chen Yang; Sven Erik Jørgensen; Fu-Liu Xu (Environmental Science and Pollution Research, 2016)

Interpreting sedimentation dynamics at Longxi catchment in the Three Gorges Area, China, using Cs-137 activity, particle size and rainfall erosivity - Jin-zhang Gao; Yi Long; Xin-bao Zhang; Adrian L. Collins; Xiu-bin He; Yun-qi Zhang; Zhong-lin Shi (Journal of Mountain Science, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Development of a multiplex event-specific PCR assay for detection of genetically modified rice - J. Lu; G.Z. Ji; G. Li; Y.F. Wu; J. Yang; S.L. Lin; D.L. Yang; J.N. Zhao; W.M. Xiu (Cereal Research Communications, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

JA, a new type of polyunsaturated fatty acid isolated from Juglans mandshurica Maxim, limits the survival and induces apoptosis of heptocarcinoma cells - Xiu-Li Gao; Hua Lin; Wei Zhao; Ya-Qin Hou; Yong-Li Bao; Zhen-Bo Song; Lu-Guo Sun; Shang-Yi Tian; Biao Liu; Yu-Xin Li (Apoptosis, 2016)

Sex Dimorphism Profile of Alzheimer’s Disease-Type Pathologies in an APP/PS1 Mouse Model - Shu-Sheng Jiao; Xian-Le Bu; Yu-Hui Liu; Chi Zhu; Qing-Hua Wang; Lin-Lin Shen; Cheng-Hui Liu; Ye-Ran Wang; Xiu-Qing Yao; Yan-Jiang Wang (Neurotoxicity Research, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

New phenyl derivatives from endophytic fungus Botryosphaeria sp. SCSIO KcF6 derived of mangrove plant Kandelia candel - Zhi-ran Ju; Xiaochu Qin; Xiu-ping Lin; Jun-feng Wang; Kumaravel Kaliyaperumal; Yong-qi Tian; Juan Liu; Fen Liu; Zhengchao Tu; Shi-hai Xu; Yonghong Liu (Natural Product Research, 2016)

Synthesis, Characterization, Properties and DFT Calculations of 2-(Benzo[b]thiophen-2-yl)pyridine-based Iridium(III) Complexes with Different Ancillary Ligands - Gao-Nan Li; Yong-Pi Zeng; Kai-Xiu Li; Hao-Hua Chen; Hui Xie; Fu-Lin Zhang; Guang-Ying Chen; Zhi-Gang Niu (Journal of Fluorescence, 2016)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Sphingobacterium rhinocerotis sp. nov., isolated from the faeces of Rhinoceros unicornis - Gui-Ding Li; Xiu Chen; Qin-Yuan Li; Fang-Ji Xu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2015)

Inhibition of myosin light chain kinase reduces NADPH oxidase-mediated oxidative injury in rat brain following cerebral ischemia/reperfusion - Hong-Feng Zhang; Ting-Bo Li; Bin Liu; Zheng Lou; Jie-Jie Zhang; Jing-Jie Peng; Xiao-Jie Zhang; Qi-Lin Ma; Jun Peng; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Invasive fungal infection in allogeneic hematopoietic stem cell transplant recipients: single center experiences of 12 years - Ji-min Shi; Xu-ying Pei; Yi Luo; Ya-min Tan; Ru-xiu Tie; Jing-song He; Wei-yan Zheng; Jie Zhang; Zhen Cai; Mao-fang Lin; He Huang (Journal of Zhejiang University-SCIENCE B, 2015)

Nitrogen and phosphorus loss and optimal drainage time of paddy field under controlled drainage condition - Meng-hua Xiao; Shuang-en Yu; Dongli She; Xiu-jun Hu; Lin-lin Chu (Arabian Journal of Geosciences, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Effect of dietary glutamine on growth performance, non-specific immunity, expression of cytokine genes, phosphorylation of target of rapamycin (TOR), and anti-oxidative system in spleen and head kidney of Jian carp (Cyprinus carpio var. Jian) - Kai Hu; Jing-Xiu Zhang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Jun Jiang; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2015)

Diaphorobacter ruginosibacter sp. nov., isolated from soybean root nodule, and emended description of the genus Diaphorobacter - Xiu Li Wei; Meng Sha Han; Cong Cong Xia; Shu Lan Ding; Lin Xu; Yan Bing Lin; Li Wang; Ge Hong Wei (Archives of Microbiology, 2015)

Ascomycotin A, a new citromycetin analogue produced by Ascomycota sp. Ind19F07 isolated from deep sea sediment - Yong-qi Tian; Xiu-ping Lin; Juan Liu; Kumaravel Kaliyaperumal; Wen Ai; Zhi-ran Ju; Bin Yang; Junfeng Wang; Xian-wen Yang; Yonghong Liu (Natural Product Research, 2015)

Inhibition of isoflavone biosynthesis enhanced T-DNA delivery in soybean by improving plant–Agrobacterium tumefaciens interaction - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Xiu-Lin Guo; Hui-Cong Li; Guo-Liang Li; Chun-Zhi Jiang; Meng-Chen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

The wheat NHX antiporter gene TaNHX2 confers salt tolerance in transgenic alfalfa by increasing the retention capacity of intracellular potassium - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Hui-Cong Li; Xiu-Lin Guo; Guo-Liang Li (Plant Molecular Biology, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Distribution of PCDD/Fs in the fly ash and atmospheric air of two typical hazardous waste incinerators in eastern China - Tong Chen; Ming-xiu Zhan; Xiao-qing Lin; Jian-ying Fu; Sheng-yong Lu; Xiao-dong Li (Environmental Science and Pollution Research, 2015)

A chimeric antibody targeting CD147 inhibits hepatocellular carcinoma cell motility via FAK-PI3K-Akt-Girdin signaling pathway - Yuan Wang; Lin Yuan; Xiang-Min Yang; Ding Wei; Bin Wang; Xiu-Xuan Sun; Fei Feng; Gang Nan; Ye Wang; Zhi-Nan Chen; Huijie Bian (Clinical & Experimental Metastasis, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Effects and Mechanism of Action of Ligustrazine on Isoprenaline-Induced Cardiomyocyte Hypertrophy - Xuan Xiu Ji; Xiao Li Song; Wei Qian; Xiao Lin Yu; Jian You Zhu (Cell Biochemistry and Biophysics, 2014)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Protective effect of vitexin compound B-1 against hypoxia/reoxygenation-induced injury in differentiated PC12 cells via NADPH oxidase inhibition - Zhong-Bao Yang; Bin Tan; Ting-Bo Li; Zheng Lou; Jun-Lin Jiang; Ying-Jun Zhou; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Effects of Bone Marrow Mesenchymal Stem Cells on Hematopoietic Recovery and Acute Graft-Versus-Host Disease in Murine Allogeneic Umbilical Cord Blood Transplantation Model - Zhen Yu Li; Chun Qing Wang; Guang Lu; Xiu Ying Pan; Kai Lin Xu (Cell Biochemistry and Biophysics, 2014)

Axinelline A, a new COX-2 inhibitor from Streptomyces axinellae SCSIO02208 - Wen Ai; Xiu-Ping Lin; Zhengchao Tu; Xin-Peng Tian; Xin Lu; Fredimoses Mangaladoss; Zhi-Long Zhong; Yonghong Liu (Natural Product Research, 2014)

Seasonal dynamics of physical and biological processes in the central California Current System: A modeling study - Lin Guo; Fei Chai; Peng Xiu; Huijie Xue; Shivanesh Rao; Yuguang Liu; Francisco P. Chavez (Ocean Dynamics, 2014)

An analysis of the resilience capacity of soils in North China: a study on land subsidence treatment - Xiu-yan Wang; Lin Sun; Zhi-liang Wang; Chang-li Liu; Yun Zhang (Bulletin of Engineering Geology and the Environment, 2014)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

Differential proteome analysis of mature and germinated seeds of Magnolia sieboldii K. Koch - Xiao-lin Zhang; Guang-lin Liu; Tian-lai Li; Ming-fang Qi; Mei Mei; Xiu-jun Lu (Trees, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Endophytic nitrogen-fixing Klebsiella variicola strain DX120E promotes sugarcane growth - Chun-Yan Wei; Li Lin; Li-Jing Luo; Yong-Xiu Xing; Chun-Jin Hu; Li-Tao Yang; Yang-Rui Li; Qianli An (Biology and Fertility of Soils, 2014)

Determinants of public goods investment in rural communities in mountainous areas of Sichuan Province, China - Shi-li Guo; Shao-quan Liu; Ren-fu Luo; Lin-xiu Zhang (Journal of Mountain Science, 2014)

Systematic position of Cyathocline Cass. (Asteraceae): evidences from molecular, cytological and morphological data - Wei-Ping Li; Feng-Ming Qian; Xiu-Lin Yang; San-Mao Chen (Plant Systematics and Evolution, 2014)

The bionomics, habitat requirements and population threats of the butterfly Bhutanitis thaidina in Taibai Mountain - Ke Gao; Xiu-shan Li; Zhen-ying Guo; Ya-lin Zhang (Journal of Insect Conservation, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

HOXA9 Gene Expression in Acute Myeloid Leukemia - De-Peng Li; Zhen-Yu Li; Wei Sang; Hai Cheng; Xiu-Ying Pan; Kai-Lin Xu (Cell Biochemistry and Biophysics, 2013)

Al-enhanced Expression and Interaction of 14-3-3 Protein and Plasma Membrane H+-ATPase is Related to Al-induced Citrate Secretion in an Al-resistant Black Soybean - Chuan-Long Guo; Qi Chen; Xiu-Ling Zhao; Xuan-qian Chen; Yan Zhao; Lin Wang; Kui-Zhi Li; Yong-Xiong Yu; Li-Mei Chen (Plant Molecular Biology Reporter, 2013)

Contrasting neuropathology and functional recovery after spinal cord injury in developing and adult rats - Qiuju Yuan; Huanxing Su; Kin Chiu; Wutian Wu; Zhi-Xiu Lin (Neuroscience Bulletin, 2013)

Genetic diversity and evolutionary characterization of Chinese porcine reproductive and respiratory syndrome viruses based on NSP2 and ORF5 - Jian-Kui Liu; Chun-Hua Wei; Xiao-Yan Yang; Xi-Lin Hou; AI-Ling Dai; Xiao-Hua Li; Mei-Kang Wei; Xiu-Zhen Pan (Archives of Virology, 2013)

Two new alkaloids from marine sponge Callyspongia sp. - Bin Yang; Huaming Tao; Xuefeng Zhou; Xiu-Ping Lin; Yonghong Liu (Natural Product Research, 2013)

Rhizobium qilianshanense sp. nov., a novel species isolated from root nodule of Oxytropis ochrocephala Bunge in China - Lin Xu; Yong Zhang; Zheng Shan Deng; Liang Zhao; Xiu Li Wei; Ge Hong Wei (Antonie van Leeuwenhoek, 2013)

Influence of gonadotropin-releasing hormone agonist on the effect of chemotherapy upon ovarian cancer and the prevention of chemotherapy-induced ovarian damage: an experimental study with nu/nu athymic mice - Qiong-yan Lin; Yi-feng Wang; Hui-nan Weng; Xiu-jie Sheng; Qing-ping Jiang; Zhi-ying Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Regulation of voltage-gated sodium current by endogenous Src family kinases in cochlear spiral ganglion neurons in culture - Shuang Feng; Melissa Pflueger; Shuang-Xiu Lin; Bradley R. Groveman; Jiping Su; Xian-Min Yu (Pflügers Archiv - European Journal of Physiology, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Bioaccessibility and Risk Assessment of Cadmium from Uncooked Rice Using an In Vitro Digestion Model - Lin-Sheng Yang; Xiu-Wu Zhang; Yong-Hua Li; Hai-Rong Li; Ying Wang; Wu-Yi Wang (Biological Trace Element Research, 2012)

A butterfly hotspot in western China, its environmental threats and conservation - Xiu-shan Li; Ya-lin Zhang; Jian-hui Fang; Oliver Schweiger; Josef Settele (Journal of Insect Conservation, 2011)

Calcitonin gene-related peptide released from endothelial progenitor cells inhibits the proliferation of rat vascular smooth muscle cells induced by angiotensin II - Li Fang; Mei-Fang Chen; Zhi-Lin Xiao; Yin Liu; Guo-Long Yu; Xiao-Bin Chen; Xiu-Mei Xie (Molecular and Cellular Biochemistry, 2011)

Systematic analysis of potato acid invertase genes reveals that a cold-responsive member, StvacINV1, regulates cold-induced sweetening of tubers - Xun Liu; Chi Zhang; Yongbin Ou; Yuan Lin; Botao Song; Conghua Xie; Jun Liu; Xiu-Qing Li (Molecular Genetics and Genomics, 2011)

Enhancement of salt tolerance in alfalfa transformed with the gene encoding for betaine aldehyde dehydrogenase - Zi-Hui Liu; Hong-Mei Zhang; Guo-Liang Li; Xiu-Lin Guo; Shou-Yi Chen; Gui-Bo Liu; Yan-Min Zhang (Euphytica, 2011)

Vulnerability of large city and its implication in urban planning: A perspective of intra-urban structure - Chunliang Xiu; Lin Cheng; Wei Song; Wei Wu (Chinese Geographical Science, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Phylogeny of Arachis based on internal transcribed spacer sequences - Chuan Tang Wang; Xiu Zhen Wang; Yue Yi Tang; Dian Xu Chen; Feng Gao Cui; Jian Cheng Zhang; Shan Lin Yu (Genetic Resources and Crop Evolution, 2011)

Pseudonocardia sichuanensis sp. nov., a novel endophytic actinomycete isolated from the root of Jatropha curcas L. - Sheng Qin; Ke Xing; Shi-Min Fei; Qiang Lin; Xiu-Min Chen; Cheng-Liang Cao; Yong Sun; Yun Wang; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2011)

Effect of blue light on indoor seedling culture of Saccharina japonica (Phaeophyta) - Wen-Jun Wang; Xiu-Tao Sun; Guang-Ce Wang; Pu Xu; Xiang-Yu Wang; Zhe-Long Lin; Fei-Jiu Wang (Journal of Applied Phycology, 2010)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

Confirmation of the relationship between plant height and Fusarium head blight resistance in wheat (Triticum aestivum L.) by QTL meta-analysis - Shuang-Lin Mao; Yu-Ming Wei; Wenguang Cao; Xiu-Jin Lan; Ma Yu; Zheng-Mao Chen; Guo-Yue Chen; You-Liang Zheng (Euphytica, 2010)

Propranolol regulates cardiac transient outward potassium channel in rat myocardium via cAMP/PKA after short-term but not after long-term ischemia - Li Zhang; Chao-Qian Xu; Yuan Hong; Jia-Lin Zhang; Ying Liu; Mei Zhao; Yan-Xiu Cao; Yan-Jie Lu; Bao-Feng Yang; Hong-Li Shan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

On the conservation biology of a Chinese population of the birdwing Troides aeacus (Lepidoptera: Papilionidae) - Xiu-shan Li; You-qing Luo; Ya-lin Zhang; Oliver Schweiger; Josef Settele; Qing-sen Yang (Journal of Insect Conservation, 2010)

The Chebyshev spectral element method using staggered predictor and corrector for elastic wave simulations - Cheng-Xuan Che; Xiu-Ming Wang; Wei-Jun Lin (Applied Geophysics, 2010)

Establishment and maintenance of three Chinese human embryonic stem cell lines - Di Zhou; Ge Lin; Chang-Qing Xie; Bo Xiong; Xiao-Ying Zhou; Xiao-Bing Qian; Yi Liao; Guang-Xiu Lu (In Vitro Cellular & Developmental Biology - Animal, 2010)

An investigation of hormesis of trichloroethylene in L-02 liver cells by differential proteomic analysis - Hai-Yan Huang; Jian-Jun Liu; Ren-Rong Xi; Xiu-Mei Xing; Jian-Hui Yuan; Lin-Qing Yang; Gong-Hua Tao; Chun-Mei Gong; Zhi-Xiong Zhuang (Molecular Biology Reports, 2009)

A 60-s postconditioning protocol by percutaneous coronary intervention inhibits myocardial apoptosis in patients with acute myocardial infarction - Wen-Shu Zhao; Lin Xu; Le-Feng Wang; Li Zhang; Zhi-Yong Zhang; Yu Liu; Xiu-Lan Liu; Xin-Chun Yang; Liang Cui; Lin Zhang (Apoptosis, 2009)

Characterization of the complete genome sequence of pike fry rhabdovirus - Hong-Lian Chen; Hong Liu; Zong-Xiao Liu; Jun-Qiang He; Long-Ying Gao; Xiu-Jie Shi; Yu-Lin Jiang (Archives of Virology, 2009)

Establishment and characterization of a fibroblast cell line from the Mongolian horse - Lin-feng Li; Wei-jun Guan; Yue Hua; Xiu-juan Bai; Yue-hui Ma (In Vitro Cellular & Developmental Biology - Animal, 2009)

Superoxide dismutase and cytokines in chronic patients with schizophrenia: association with psychopathology and response to antipsychotics - Xiang Yang Zhang; Dong Feng Zhou; Ling Yan Qi; Song Chen; Lian Yuan Cao; Da Chun Chen; Mei Hong Xiu; Fan Wang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

SCI citation analysis and impact factor prediction of JZUS-B in 2008 - Han-feng Lin; Xiu-fang Wu; Yue-hong Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

Lower serum cytokine levels in smokers than nonsmokers with chronic schizophrenia on long-term treatment with antipsychotics - Xiang Yang Zhang; Lian Yuan Cao; Cai Song; Gui Ying Wu; Da Chun Chen; Ling Yan Qi; Fan Wang; Mei Hong Xiu; Song Chen; Yingyang Zhang; Lin Lu; Therese A. Kosten; et al. (Psychopharmacology, 2008)

Hypertonic saline resuscitation reduces apoptosis of intestinal mucosa in a rat model of hemorrhagic shock - Yuan-qiang Lu; Wei-dong Huang; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2008)

An analytical algorithm with a wave age factor for altimeter wind speed retrieval - Yongcun Cheng; Qing Xu; Yuguang Liu; Hui Lin; Peng Xiu; Xiaobin Yin; Haibo Zong; Zengrui Rong (International Journal of Remote Sensing, 2008)

Genetic dissection and pyramiding of quantitative traits for panicle architecture by using chromosomal segment substitution lines in rice - Tsuyu Ando; Toshio Yamamoto; Takehiko Shimizu; Xiu Fang Ma; Ayahiko Shomura; Yoshinobu Takeuchi; Shao Yang Lin; Masahiro Yano (Theoretical and Applied Genetics, 2008)

Molecular Characterization and Expression Pattern of Two Pheromone-Binding Proteins from Spodoptera litura (Fabricius) - Wei-Ming Xiu; Yao-Zhen Zhou; Shuang-Lin Dong (Journal of Chemical Ecology, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

Solid Substrate–Room Temperature Phosphorimetry for the Determination of Trace Terbutaline Sulfate Based on Its Inhibition Oxidation of Rhodamine 6G by Sodium Periodate - Jia-Ming Liu; Fei Gao; Wen-Yan Gao; Li-Qing Zeng; Xiao-Mei Huang; Zhi-Ming Li; Xiu-Chai Huang; Wei-Nv Lin; Fang-Mei Wang; Chang-Ling Nie (Journal of Fluorescence, 2008)

A follow-up study of mortality among the arseniasis patients exposed to indoor combustion of high arsenic coal in Southwest Guizhou Autonomous Prefecture, China - Ji-gang Chen; Yu-gang Chen; Yun-shu Zhou; Guo-fang Lin; Xiu-jie Li; Chao-gang Jia; Wei-chao Guo; Hui Du; Hong-chao Lu; Hong Meng; Xin-jiang Zhang; Klaus Golka; et al. (International Archives of Occupational and Environmental Health, 2007)

Adaptation of agriculture to warming in Northeast China - Xiu Yang; Erda Lin; Shiming Ma; Hui Ju; Liping Guo; Wei Xiong; Yue Li; Yinlong Xu (Climatic Change, 2007)

Molecular Characterization of Two Pheromone Binding Proteins and Quantitative Analysis of their Expression in the Beet Armyworm, Spodoptera exigua Hübner - Wei-Ming Xiu; Shuang-Lin Dong (Journal of Chemical Ecology, 2007)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Induction of G2/M phase arrest and apoptosis by a novel enediyne derivative, THDA, in chronic myeloid leukemia (K562) cells - Zchong-Zcho Wu; Ching-Ming Chien; Sheng-Huei Yang; Yi-Hsiung Lin; Xiu-Wei Hu; Yu-Jhang Lu; Ming-Jung Wu; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2006)

External sources of urban competitive advantages in China - Tao-fang Yu; Chao-lin Gu; Xiu-ying Chen (Chinese Geographical Science, 2005)

Germplasm improvement for preharvest sprouting resistance in Chinese white-grained wheat: An overview of the current strategy - Shi-He Xiao; Xiu-Ying Zhang; Chang-Sheng Yan; Hai Lin (Euphytica, 2002)